Roman Mosaics in the J. Paul Getty Museum - Alexis Belis (Getty Publications, 2016)
The mosaics in the collection of the J. Paul Getty Museum span the second through the sixth centuries AD and reveal the diversity of compositions found throughout the Roman Empire during this period. Elaborate floors of stone and glass tesserae transformed private dwellings and public buildings alike into spectacular settings of vibrant color, figural imagery, and geometric design. Scenes from mythology, nature, daily life, and spectacles in the arena enlivened interior spaces and reflected the cultural ambitions of wealthy patrons. This online catalogue documents all of the mosaics in the Getty Museum